Educação e resistência anarquista em São Paulo: a sobrevivência das práticas da educação libertária na Academia de Comércio Saldanha Marinho (1920 1945) - Fregoni, Olga Regina (2007)
This dissertation aims to demonstrate the subsisting rationalist principles and methods, which overcame the closure of the Escolas Modernas (Modern Schools) of São Paulo, starting a discussion with the Brazilian historiography which considers such experiments finished in 1919. In order to achieve this goal, we analyzed the set of scholastic attitudes present in the Academia de Comércio Saldanha , which was founded by the anarchist João Penteado, trying to recognize some continuity in the remaining of this experiment, between the years of 1920 and 1945. The temporal selection is justified by the encompassing period of intense debate about education issues in Brazil. To this analysis, we utilized the school journals, João Penteado s manuscripts and the scholastic administrative documentation which are current located at the Centro de Memória da Escola da Universidade de São Paulo (Memorial Center of the São Paulo University s School). We tried to link the anarchist proposal continuity to the resistance forms present in the liberating associations, understanding them as part of the ideal and culture of the anarchist period